Dampak Peremajaan Sawit Rakyat (PSR) Terhadap Kesejahteraan Petani Kelapa Sawit Di LabuanBatu Utara, Sumatera Utara - Putri, Rahmi Eka; Siregar, Ameilia Zuliyanti; Mahera, Isma Yudi (Jurnal KIRANA, 2023)
Palm oil is a leading commodity in North Sumatra, but the age of oil palm plants was old and must be immediately rejuvenated From surveys and identification problems of palm oil plantation with farmers in South Kualuh District, North Batu Regency, farmers are constrained by capital and knowledge for oil palm plant rejuvenation. The purpose of this study is to determine the welfare impact of oil palm farmers in the implementation of the smallholder oil palm replanting program (PSR) and determine the factors that influence the impact of smallholder oil palm replanting (PSR) on the welfare of oil palm farmers and will be carried out from March 20 to May 31, 2023. The sampling technique uses proportional random sampling with 52 respondents. Data collection method with questionnaires tested for validity and reliability. The data analysis method uses the Paired T test and Multiple Linear Regression Test. The results showed that there was a difference in the average income of farmers before and after participating in the Smallholder Palm Oil Replanting (PSR) program where based on the results of the Paired T test obtained a significance value of ≤ 0.05 and a t-value calculated > t table that shows smallholder oil palm replanting (PSR) can improve the welfare of oil palm farmers. variables Consumption Patterns, FFB Prices, Capital Assistance, and variables The availability of study programs has a significant effect and positive value. However, the variables Land Area and Income have a partial effect and are negative. This shows that the variables of Land Area and Income have a negative or inverse proportion to the Impact of Smallholder oil Replanting (ISR) on the welfare of oil palm farmers in South Kualuh District.